Prevalence of H.pylori in the Arab world - Abdallah, TajEldin M; Mohammed, Habib Allah H; Elwasila, Walid A; Ali, Khalid M; Omer, Saeed M; Mohammed, Amira A (مجلة الجزيرة للعلوم الصحية; مجلد 14 عدد 1 (2018), 2018)
Aim : To investigate prevalence of Helicobacter pylori ( H. pylor i) among healthy asymptomatic and symptomatic patients in the Arab world. Where H.pylori infection constitutes a real heath problem. Methods : A computerized comprehensive English language literature search of Pub Med, Scopus, and Google scholar was carried out in April 2016, evaluating the prevalence of H.pylori in the Arab countries. Results In the electronic search, a total of 100 papers were initially identified. And after evaluating the titles, abstracts and full text of relevant articles.44 papers were included in this review Conclusion : This review demonstrated high prevalence of H.pylori infection among symptomatic and asymptomatic people of the Arab world, immediate intervention should be made regarding identification, eradication and prevention of this bacterium. الهدف:هدفت هذه الدراسة  لدراسة معدل انتشار الملتوية البوابية بين المرضى الذين يعانون أعراض و الا صحاء في العالم العربي. حيث تشكل بكتيريا الملتوية البوابية مشكلة صحية  حقيقية                                                               الطريقة: تم إجراء بحث محوسب شامل في اللغة الإنجليزية لأبحاث بوب ميد، سكوبوس، و غوغل سشولار في أبريل 2016، لتقييم معدل انتشار بكتيريا الملتوية البوابية في البلدان العربية    .النتائج: بعد البحث الالكترونى تم الحصول على 100 ورقة وبعد تقييمها 44 ورقة وجدت مناسبة لتتضمن فى دراسة المراجعة هذه  الخلاصة: هذه المراجعة أظهرت ارتفاع معدل انتشار بكتيريا الملتوية البوابية بين الناس سواء كانوا يعانون من أعراض او بدون أعراض في العالم العربي، وينبغي بذل التدخل الفوري فيما يتعلق بتحديد والاستئصال والوقاية من هذه البكتيريا